Parvovirus infection associated with aplastic crisis in a patient with HEMPAS. Issue 9 (September 1986) - West, N C; Meigh, R E; Mackie, M; Anderson, M J
Abstract : An aplastic crisis associated with parvovirus infection occurred in a patient suffering from hereditary erythrocytic multinuclearity associated with a positive acidified (Hams) test (HEMPAS). This case emphasises that any patient who has a shortened red cell survival is susceptible to an aplastic crisis induced by parvovirus.